A low-VOC automotive sealing strip composite PVC material and preparation method thereof

By adding modified mesoporous ZIF-8 nanomaterial and composite filler to the substrate of the automotive seal strip, the problems of poor thermal aging resistance and release of volatile organic compounds are solved, and higher flame retardant performance, thermal aging resistance and mechanical properties are achieved.

CN119241967BActive Publication Date: 2025-04-01ZHEJIANG XINGYU AUTO PARTS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411789314.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-01
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing automobile seal strips have poor heat-resistant aging performance, are prone to cracking, and release harmful gases during the aging process, and release volatile organic compounds during the processing process, affecting the mechanical properties.

Method used

PVC resin and ethylene propylene ternary rubber were used as the substrate, and modified mesoporous ZIF-8 nanomaterial and composite filler were added. The antioxidant components were grafted on the surface of mesoporone diisocyanate as the bridge agent, and modified nanosilica and aminolated basalt fibers were grafted to improve the flame retardant, heat-resistant aging and mechanical properties of the material.

Benefits of technology

It significantly improves the flame retardant performance, heat-resistant aging and mechanical properties of the automotive seal strip, while reducing the release of volatile organic compounds, improving the stability and safety of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of sealing strips, and discloses a low-VOC automobile sealing strip composite PVC material and a preparation method thereof. The material comprises: PVC resin, ethylene propylene diene monomer rubber, modified mesoporous ZIF-8 nanomaterial, composite filler, etc. The modified mesoporous ZIF-8 nanomaterial is prepared by grafting a hydroxylated antioxidant component on the surface of the mesoporous ZIF-8 nanomaterial using isophorone diisocyanate, and the hydroxylated antioxidant component is prepared by reacting N-(4-anilinophenyl) maleimide and 2-mercaptoethanol; the composite filler is prepared by grafting modified nano silicon dioxide and amino basalt fiber, the modified nano silicon dioxide is prepared by using phenylphosphoryl dichloride, diethanolamine, dibutyl phosphate and isophorone diisocyanate as raw materials, and the amino basalt fiber is modified by using an amino silane coupling agent. The modified mesoporous ZIF-8 nanomaterial and the composite filler are added to improve the flame retardant property, heat aging resistance and mechanical property of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sealing strips, and in particular relates to a low-VOC automobile sealing strip composite PVC material and a preparation method thereof. Background Art

[0002] Automobile sealing strips are one of the important parts of automobiles. They can fill various gaps and crevices between the components of the automobile body. They have the functions of shock absorption, waterproofing, dustproofing, sound insulation, decoration, etc., which can improve the comfort of driving experience and protect the car body. According to the material type, they can be divided into rubber sealing strips, plastic sealing strips and thermoplastic elastomer sealing strips. With the continuous development of science and technology, the automotive industry has higher and higher technical requirements for automobile sealing strips, which not only require them to have high sealing performance, but also require products to have high mechanical properties, anti-aging, flame retardant and other properties.

[0003] Existing automotive sealing strips mainly use PVC, natural rubber, EPDM rubber and silicone. Among them, the main component of PVC sealing strips is polyvinyl chloride, and other ingredients such as plasticizers are added to enhance its heat resistance, toughness, ductility, etc. PVC sealing strips have the characteristics of easy molding, recyclability, and reusability. They have been widely used in manufacturing industries such as automobiles, doors and windows, and curtain walls. However, PVC sealing strips have poor heat aging resistance and are prone to cracking. The aging process of PVC will release harmful gas hydrogen chloride. In addition, the raw materials and additives in PVC sealing strips will release volatile organic compounds due to high temperature and shear force during the processing process.

[0004] The existing technology improves the odor release problem of sealing strip products by adding deodorants or photocatalyst technology, including the use of zeolite, carbon black, bentonite, fly ash and titanium dioxide. In order to improve the deodorization effect, it is necessary to increase the amount of deodorant added to the matrix. Due to the difference in the interface properties between the inorganic deodorant and the matrix, a higher amount of deodorant added can easily lead to a decrease in the mechanical properties of the sealing strip. Summary of the invention

[0005] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a low-VOC automotive sealing strip composite PVC material and a preparation method thereof, using PVC resin and EPDM rubber as a base material, and adding modified mesoporous ZIF-8 nanomaterials and composite fillers to give the material excellent flame retardant properties, heat aging resistance and mechanical properties.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A low-VOC automobile sealing strip composite PVC material, comprising the following raw materials in parts by weight: 70-90 parts of PVC resin, 10-30 parts of EPDM rubber, 5-10 parts of modified mesoporous ZIF-8 nanomaterials, 2-6 parts of composite fillers, 4-7 parts of heat stabilizers, 10-20 parts of plasticizers, and 1-3 parts of lubricants;

[0008] The modified mesoporous ZIF-8 nanomaterial is prepared by using isophorone diisocyanate as a bridging agent to graft a hydroxylated antioxidant component onto the surface of the mesoporous ZIF-8 nanomaterial, wherein the hydroxylated antioxidant component is prepared by using an antioxidant N-(4-anilinophenyl) maleimide and 2-mercaptoethanol to undergo a thiol-ene click reaction;

[0009] The composite filler is made by grafting modified nano-silica with amino basalt fiber through chemical reaction, wherein the modified nano-silica is made by chemical reaction with phenylphosphinoyl dichloride, diethanolamine, dibutyl phosphate and isophorone diisocyanate as raw materials, and the amino basalt fiber is made by modification with 3-aminopropyltriethoxysilane.

[0010] Preferably, the heat stabilizer is a calcium zinc stabilizer; the plasticizer is one or more combinations of di(2-propylheptyl)phthalate, 911 phthalate, and dinonyl sebacate; and the lubricant is one or more combinations of stearic acid, polyethylene wax, and oxidized polyethylene wax.

[0011] Preferably, the preparation method of the modified mesoporous ZIF-8 nanomaterial comprises the following steps:

[0012] (1) Dissolve zinc acetate dihydrate in a polyvinyl pyrrolidone aqueous solution with a mass fraction of 3-5 wt.%, then add n-octanol and mix at a speed of 10000-22000 rpm for 4-7 min to form a mixed solution, dissolve 2-methylimidazole in n-octanol under ultrasonic action and add it to the mixed solution, mix at a speed of 9000-12000 rpm for 0.5-1 min, let it stand for 5-9 h, and then centrifuge, wash, and dry to prepare a mesoporous ZIF-8 nanomaterial;

[0013] (2) N-(4-anilinophenyl)maleimide and 2-mercaptoethanol are dissolved in tetrahydrofuran, and then triethylamine is added. The mixture is stirred at 50-60°C in a nitrogen atmosphere for 5-8 hours. After the reaction is completed, the mixture is rotary evaporated and dried to obtain a hydroxylated antioxidant component.

[0014] (3) taking the hydroxylated antioxidant component and isophorone diisocyanate into a reactor, adding toluene solvent and dibutyltin diacetate, placing the mixture at 55-70°C and stirring for 5-8 hours, and after the reaction is completed, rotary evaporation and drying are performed to prepare the isocyanate antioxidant component;

[0015] (4) The mesoporous ZIF-8 nanomaterial is ultrasonically dispersed in toluene, and then the isocyanate-treated antioxidant component is added and stirred to react for 3 to 5 hours. After the reaction is completed, the modified mesoporous ZIF-8 nanomaterial is prepared by filtering, washing, and drying.

[0016] Preferably, in step (2), the molar ratio of N-(4-anilinophenyl)maleimide to 2-mercaptoethanol is 1:1-2.

[0017] Preferably, in step (3), the molar ratio of the hydroxylated antioxidant component to isophorone diisocyanate is 1-1.2:1.

[0018] Preferably, in step (4), the mass ratio of the mesoporous ZIF-8 nanomaterial to the isocyanate-treated antioxidant component is 1:1-3.

[0019] Preferably, the method for preparing the composite filler comprises the following steps:

[0020] A. Phenylphosphoryl dichloride and diethanolamine are placed in a reactor, tetrahydrofuran solvent and triethylamine are added, and the mixture is stirred for reaction for 5-8 hours. After the reaction is completed, the mixture is filtered, rotary evaporated, and dried to obtain component 1. Dibutyl phosphate is placed in a reactor, the temperature is raised to 70-90°C, isophorone diisocyanate and dibutyltin dilaurate are added to react for 1-3 hours, and then the temperature is lowered to room temperature, component 1 is added to continue the reaction for 0.5-1 hour, and after the reaction is completed, the mixture is washed and dried to obtain a double-terminated hydroxyl flame retardant component;

[0021] B. Put hexamethylene diisocyanate in a reactor, add toluene solvent to dissolve, heat to 75-85°C, pass nitrogen protection, dissolve the double-terminal hydroxyl flame retardant component and dibutyltin dilaurate in toluene and add them to the reactor, stir and react for 1-2 hours to obtain a prepolymer, ultrasonically disperse nano-silicon dioxide in toluene, then add it to the prepolymer, stir and react at 70-85°C for 1-2 hours, filter, wash and dry after the reaction is completed to prepare modified nano-silicon dioxide;

[0022] C. Ultrasonic dispersion of basalt fiber in anhydrous ethanol, adding 3-aminopropyltriethoxysilane and deionized water, and then stirring and reacting at 60-80°C for 5-7h. After the reaction is completed, centrifugation, washing and drying are performed to prepare amino basalt fiber;

[0023] D. Take the amino basalt fiber and ultrasonically disperse it in toluene, add modified nano-silica and dibutyltin dilaurate to disperse evenly, place it at 50-70°C and stir to react for 10-12 hours. After the reaction is completed, filter, wash and dry to prepare a composite filler.

[0024] Preferably, in step A, the molar ratio of phenylphosphoryl dichloride, diethanolamine, dibutyl phosphate and isophorone diisocyanate is 1:2-2.5:2-2.7:2-2.5.

[0025] Preferably, in step B, the mass ratio of hexamethylene diisocyanate, the dihydroxyl-terminated flame retardant component and the nano-silicon dioxide is 1:3.5-3.7:4-8.

[0026] The preparation method of the low-VOC automobile sealing strip composite PVC material as described above comprises the following steps: taking parts by weight of PVC resin, EPDM rubber, modified mesoporous ZIF-8 nanomaterial, composite filler, heat stabilizer, plasticizer and lubricant and mixing them evenly to form a premix, melting the premix, granulating and then extruding the premix to prepare the low-VOC automobile sealing strip composite PVC material.

[0027] Beneficial effects of the present invention:

[0028] The invention firstly adopts a soft template method to prepare a mesoporous ZIF-8 nanomaterial with high porosity and large surface area, then uses an antioxidant N-(4-anilinophenyl) maleimide and 2-mercaptoethanol to undergo a thiol-ene click reaction to prepare a hydroxylated antioxidant component, and uses isophorone diisocyanate as a bridging agent to graft the isocyanate groups in its structure with the hydroxylated antioxidant component and the mesoporous ZIF-8 nanomaterial to prepare a modified mesoporous ZIF-8 nanomaterial, thereby grafting the antioxidant component on the surface of the mesoporous ZIF-8 nanomaterial through a strong chemical bond, thereby preventing the antioxidant component from being easily volatilized, migrated and extracted during processing or long-term use. The problem is solved, and the prepared modified mesoporous ZIF-8 nanomaterial has the advantages of large specific surface area, good stability and good compatibility with polymers, etc. It has excellent gas adsorption effect, has a strong adsorption capacity for low-molecular organic compounds, and will not desorb at higher temperatures. In addition, the modified mesoporous ZIF-8 nanomaterial will generate water vapor and oxides under high temperature to form a protective oxide layer. Zinc can promote thermal decomposition and dehydrogenation, thereby effectively promoting the formation of a carbon layer and reducing the flammability of the material. The mesoporous ZIF-8 nanomaterial is modified, so that the compatibility of the mesoporous ZIF-8 nanomaterial with the matrix is ​​improved, and the flame retardant efficiency is improved while maintaining the mechanical and thermal properties.

[0029] The present invention utilizes phenylphosphoryl dichloride and diethanolamine to undergo substitution reaction to obtain component one, and simultaneously utilizes hydroxyl groups in a dibutyl phosphate structure and isocyanate groups connected to a methylene group in an isophorone diisocyanate structure to undergo grafting reaction, and the remaining isocyanate groups further react with secondary amine groups in the structure of component one to prepare a double-terminated hydroxyl flame-retardant component, which is then introduced into a polyurethane molecular chain terminated with an isocyanate group and nano-silicon dioxide is modified, and the modified nano-silicon dioxide further reacts with the surface of a basalt fiber modified with 3-aminopropyltriethoxysilane to prepare a composite filler, wherein the introduced nitrogen and phosphorus elements greatly improve the flame retardant performance of the material, and the introduction of the polyurethane polar molecular chain improves the surface energy of the basalt fiber, and significantly improves the surface wettability of the basalt fiber, and the modified nano-silicon dioxide and the basalt fiber are combined through a strong chemical bond, which is beneficial to improving the dispersion uniformity and interface bonding strength of nano-particles on the surface of the basalt fiber, and fully exerting the mechanical properties of the nano-silicon dioxide. The present invention uses PVC resin and EPDM rubber as substrates, and the addition of modified mesoporous ZIF-8 nanomaterials and composite fillers improves the flame retardancy, heat aging resistance and mechanical properties of the material. In addition, a low-odor calcium zinc stabilizer and a plasticizer with low volatility are selected. Since the substrate components contain non-toxic and chemically stable inorganic components, the volatilization of VOC of the substrate is greatly reduced. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1 A method for preparing a modified mesoporous ZIF-8 nanomaterial comprises the following steps:

[0032] (1) 0.39 g of zinc acetate dihydrate was dissolved in 15 mL of a 4 wt.% polyvinyl pyrrolidone aqueous solution, and then 250 mL of n-octanol was added and mixed at 12000 rpm for 5 min to form a mixed solution. 1.2 g of 2-methylimidazole was dissolved in 50 mL of n-octanol under ultrasonication and then added to the mixed solution. The mixture was mixed at 10000 rpm for 1 min and allowed to stand for 7 h. The mixture was then centrifuged, washed and dried to prepare a mesoporous ZIF-8 nanomaterial.

[0033] (2) 5.28 g of N-(4-anilinophenyl)maleimide and 3.12 g of 2-mercaptoethanol were dissolved in 100 mL of tetrahydrofuran, and then 0.08 g of triethylamine was added. The mixture was stirred at 55 °C in a nitrogen atmosphere for 7 h. After the reaction was completed, the mixture was rotary evaporated and dried to prepare a hydroxylated antioxidant component.

[0034] (3) 3.76 g of hydroxylated antioxidant component and 2.22 g of isophorone diisocyanate were placed in a reactor, 50 mL of toluene solvent and 0.63 g of dibutyltin diacetate were added, and the mixture was stirred at 70 °C for 6 h. After the reaction was completed, the mixture was rotary evaporated and dried to prepare an isocyanate antioxidant component;

[0035] (4) 1.5 g of mesoporous ZIF-8 nanomaterial was ultrasonically dispersed in 100 mL of toluene, and then 3.3 g of

[0036] The isocyanate-treated antioxidant component was stirred and reacted for 5 hours. After the reaction was completed, the modified mesoporous ZIF-8 nanomaterial was prepared by filtering, washing and drying.

[0037] Example 2 A method for preparing a composite filler comprises the following steps:

[0038] A. Take 1.95g of phenylphosphoryl dichloride and 2.42g of diethanolamine in a reactor, add 100mL of tetrahydrofuran solvent and 2.12g of triethylamine, stir and react for 7h. After the reaction is completed, filter, rotary evaporate and dry to obtain component one. Take 5.25g of dibutyl phosphate in a reactor, heat to 85°C, add 5.55g of isophorone diisocyanate and 0.04g of dibutyltin dilaurate to react for 2h, then cool to room temperature, add component one and continue to react for 1h. After the reaction is completed, wash and dry to prepare a double-terminated hydroxyl flame retardant component;

[0039] B. Take 3.36g of hexamethylene diisocyanate in a reactor, add 50mL of toluene solvent to dissolve, heat to 80°C, pass nitrogen protection, take 11.97g of double-terminal hydroxyl flame retardant component and 0.02g of dibutyltin dilaurate, dissolve in 100mL of toluene, add to the reactor, stir and react for 2h to obtain a prepolymer, take 5g of nano-silicon dioxide, ultrasonically disperse in 100mL of toluene, then add to the prepolymer, place at 80°C and stir to react for 2h, filter, wash and dry after the reaction is completed to prepare modified nano-silicon dioxide;

[0040] C. Take 10g of basalt fiber and ultrasonically disperse it in 200mL of anhydrous ethanol, add 1g of 3-aminopropyltriethoxysilane and 7mL of deionized water, and then stir and react at 70°C for 6h. After the reaction is completed, centrifuge, wash and dry to prepare amino basalt fiber;

[0041] D. Take 10g of amino basalt fiber and disperse it in 200mL of toluene by ultrasonic. Add 5g of modified nano-silica and 0.04g of dibutyltin dilaurate and disperse them evenly. Stir and react at 60°C for 12h. After the reaction is completed, filter, wash and dry to prepare a composite filler.

[0042] Example 3 A low-VOC automotive sealing strip composite PVC material comprises the following raw materials in parts by weight: 72 parts of PVC resin, 14 parts of EPDM rubber, 5 parts of modified mesoporous ZIF-8 nanomaterial prepared in Example 1, 2 parts of composite filler prepared in Example 2, 4 parts of calcium zinc stabilizer, 10 parts of plasticizer di(2-propylheptyl)phthalate, and 1 part of lubricant stearic acid;

[0043] The method for preparing the low-VOC automobile sealing strip composite PVC material comprises the following steps:

[0044] Parts by weight of PVC resin, EPDM rubber, modified mesoporous ZIF-8 nanomaterial, composite filler, calcium zinc stabilizer, plasticizer and lubricant are mixed evenly to form a premix, and the premix is ​​melted, granulated and then extruded to prepare a low-VOC automotive sealing strip composite PVC material.

[0045] Example 4 A low-VOC automotive sealing strip composite PVC material comprises the following raw materials in parts by weight: 78 parts of PVC resin, 22 parts of EPDM rubber, 7 parts of modified mesoporous ZIF-8 nanomaterial prepared in Example 1, 3 parts of composite filler prepared in Example 2, 5 parts of calcium zinc stabilizer, 15 parts of plasticizer phthalate 911 ester, and 2 parts of lubricant polyethylene wax;

[0046] The preparation method of the low-VOC automotive sealing strip composite PVC material is the same as that of Example 3.

[0047] Example 5 A low-VOC automotive sealing strip composite PVC material comprises the following raw materials in parts by weight: 87 parts of PVC resin, 28 parts of EPDM rubber, 9 parts of modified mesoporous ZIF-8 nanomaterial prepared in Example 1, 6 parts of composite filler prepared in Example 2, 7 parts of calcium zinc stabilizer, 18 parts of plasticizer dinonyl sebacate, and 3 parts of lubricant oxidized polyethylene wax;

[0048] The preparation method of the low-VOC automotive sealing strip composite PVC material is the same as that of Example 3.

[0049] Comparative Example 1 A low-VOC automotive sealing strip composite PVC material comprises the following raw materials in parts by weight: 87 parts of PVC resin, 28 parts of EPDM rubber, 9 parts of the mesoporous ZIF-8 nanomaterial prepared in Example 1, 6 parts of the composite filler prepared in Example 2, 7 parts of a calcium zinc stabilizer, 18 parts of a plasticizer dinonyl sebacate, and 3 parts of a lubricant oxidized polyethylene wax;

[0050] The preparation method of the low-VOC automotive sealing strip composite PVC material is the same as that of Example 3.

[0051] Comparative Example 2 A low-VOC automotive sealing strip composite PVC material comprises the following raw materials in parts by weight: 87 parts of PVC resin, 28 parts of EPDM rubber, 9 parts of modified mesoporous ZIF-8 nanomaterial prepared in Example 1, 2 parts of modified nano-silicon dioxide prepared in Example 2, 4 parts of basalt fiber, 7 parts of calcium zinc stabilizer, 18 parts of plasticizer dinonyl sebacate, and 3 parts of lubricant oxidized polyethylene wax;

[0052] The preparation method of the low-VOC automotive sealing strip composite PVC material is the same as that of Example 3.

[0053] Comparative Example 3 A low-VOC automotive sealing strip composite PVC material comprises the following raw materials in parts by weight: 87 parts of PVC resin, 28 parts of EPDM rubber, 9 parts of modified mesoporous ZIF-8 nanomaterial prepared in Example 1, 2 parts of nano silicon dioxide, 4 parts of basalt fiber, 7 parts of calcium zinc stabilizer, 18 parts of plasticizer dinonyl sebacate, and 3 parts of lubricant oxidized polyethylene wax;

[0054] The preparation method of the low-VOC automotive sealing strip composite PVC material is the same as that of Example 3.

[0055] Performance Testing

[0056] (1) Mechanical properties and flame retardant properties testing: The automotive sealing strip composite PVC materials prepared in Examples 3-5 and Comparative Examples 1-3 were subjected to a tensile properties test using a universal mechanical testing machine in accordance with GB / T 1040.2-2022; an impact strength test was performed in accordance with GB / T1843-2008; a tear strength test was performed in accordance with GB / T 529-2008; and a Shore A hardness test was performed in accordance with GB / T 531.1-2008. The flame retardant properties were tested using a limiting oxygen index test and a vertical burning test, and the data results are shown in Table 1.

[0057] (2) Odor evaluation: The automotive sealing strip composite PVC materials prepared in Examples 3-5 and Comparative Examples 1-3 were placed in a 10L Tedlar test bag, sealed and left to stand for 3 h under an environmental condition of 70±2°C, and then odor was evaluated in accordance with Q / JLY J7110274B-20144 "Determination Method for Volatile Organic Compounds in Automotive Interior Components" (half level is allowed between levels 4 and 7), level 1 - unbearable; 2 - very disgusting; 3 - disgusting; 4 - disgusting; 5 - somewhat unbearable; 6 - tolerable; 7 - not disgusting; 8 - odor can be felt, but not obvious; 9 - almost no odor can be felt; 10 - no odor. The data results are shown in Table 1.

[0058] Table 1 Test results of mechanical properties and flame retardant properties of samples

[0059]

[0060] As can be seen from the data in Table 1, the materials prepared in Examples 3-5 of the present invention have low odor and excellent mechanical properties and flame retardant properties. In Comparative Example 1, the mesoporous ZIF-8 nanomaterial was not modified, and its measured mechanical properties were slightly worse than those of Examples 3-5, because the compatibility of the mesoporous ZIF-8 nanomaterial with the matrix was poor. In Comparative Example 2, the modified nano-silicon dioxide and basalt fiber were directly mixed, and its measured mechanical properties were lower than those of Examples 3-5, because the modified nano-silicon dioxide and basalt fiber were grafted to improve the dispersion uniformity and interface bonding strength of the nanoparticles on the surface of the basalt fiber, so that its mechanical properties were fully exerted. In Comparative Example 3, the nano-silicon dioxide and basalt fiber were directly mixed, and its measured mechanical properties were most significantly lower than those of Examples 3-5, and the flame retardant properties were lower than those of Examples 3-5, because the nano-silicon dioxide was not modified and grafted with the basalt fiber.

[0061] (3) Heat aging resistance test: The automotive sealing strip composite PVC materials prepared in Examples 3-5 and Comparative Examples 1-3 were subjected to hot air aging test according to GB / T 21282-2007. The experimental instrument was a 401B heat aging test chamber. The heat aging time was 24 h and 48 h, and the temperature was 100°C. The changes in tensile strength and elongation at break were tested. The data results are shown in Table 2.

[0062] Table 2 Test results of heat aging resistance of samples

[0063]

[0064] It can be seen from the data in Table 2 that the materials prepared in Examples 3-5 of the present invention still have high tensile strength and elongation at break after aging for 24h and 48h, and have excellent heat aging resistance. Among them, the mesoporous ZIF-8 nanomaterial in Comparative Example 1 is not grafted with an antioxidant component, and its tensile strength and elongation at break after thermal aging are measured to decrease significantly.

[0065] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0066] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A low VOC automotive sealing strip composite PVC material, characterized in that: The invention comprises the following raw materials in parts by weight: 70-90 parts of PVC resin, 10-30 parts of EPDM rubber, 5-10 parts of modified mesoporous ZIF-8 nanomaterials, 2-6 parts of composite fillers, 4-7 parts of heat stabilizers, 10-20 parts of plasticizers, and 1-3 parts of lubricants; The modified mesoporous ZIF-8 nanomaterial is prepared by using isophorone diisocyanate as a bridging agent to graft a hydroxylated antioxidant component onto the surface of the mesoporous ZIF-8 nanomaterial, wherein the hydroxylated antioxidant component is prepared by using an antioxidant N-(4-anilinophenyl) maleimide and 2-mercaptoethanol to undergo a thiol-ene click reaction; The preparation method of the composite filler comprises the following steps: A. Phenylphosphoryl dichloride and diethanolamine are placed in a reactor, tetrahydrofuran solvent and triethylamine are added, and the mixture is stirred for reaction for 5-8 hours. After the reaction is completed, the mixture is filtered, rotary evaporated, and dried to obtain component 1. Dibutyl phosphate is placed in a reactor, the temperature is raised to 70-90°C, isophorone diisocyanate and dibutyltin dilaurate are added to react for 1-3 hours, and then the temperature is lowered to room temperature, component 1 is added to continue the reaction for 0.5-1 hour, and after the reaction is completed, the mixture is washed and dried to obtain a double-terminated hydroxyl flame retardant component; B. Put hexamethylene diisocyanate in a reactor, add toluene solvent to dissolve, heat to 75-85°C, pass nitrogen protection, dissolve the double-terminal hydroxyl flame retardant component and dibutyltin dilaurate in toluene and add them to the reactor, stir and react for 1-2 hours to obtain a prepolymer, ultrasonically disperse nano-silicon dioxide in toluene, then add it to the prepolymer, stir and react at 70-85°C for 1-2 hours, filter, wash and dry after the reaction is completed to prepare modified nano-silicon dioxide; C. Ultrasonic dispersion of basalt fiber in anhydrous ethanol, adding 3-aminopropyltriethoxysilane and deionized water, and then stirring and reacting at 60-80°C for 5-7h. After the reaction is completed, centrifugation, washing and drying are performed to prepare amino basalt fiber; D. Ultrasonic dispersion of amino basalt fiber in toluene, adding modified nano-silica and dibutyltin dilaurate to disperse evenly, stirring and reacting at 50-70°C for 10-12h, filtering, washing and drying after the reaction to obtain a composite filler; In the step A, the molar ratio of phenylphosphoryl dichloride, diethanolamine, dibutyl phosphate and isophorone diisocyanate is 1:2-2.5:2-2.7:2-2.5; In the step B, the mass ratio of hexamethylene diisocyanate, the double-terminal hydroxyl flame retardant component and the nano-silicon dioxide is 1:3.5-3.7:4-8.

2. The low VOC automotive sealing strip composite PVC material according to claim 1, characterized in that: The heat stabilizer is a calcium zinc stabilizer; the plasticizer is one or more combinations of di(2-propylheptyl)phthalate, 911 phthalate, and dinonyl sebacate; the lubricant is one or more combinations of stearic acid, polyethylene wax, and oxidized polyethylene wax.

3. The low VOC automotive sealing strip composite PVC material according to claim 1, characterized in that: The preparation method of the modified mesoporous ZIF-8 nanomaterial comprises the following steps: (1) Dissolve zinc acetate dihydrate in a polyvinyl pyrrolidone aqueous solution with a mass fraction of 3-5 wt.%, then add n-octanol and mix at a speed of 10000-22000 rpm for 4-7 min to form a mixed solution, dissolve 2-methylimidazole in n-octanol under ultrasonic action and add it to the mixed solution, mix at a speed of 9000-12000 rpm for 0.5-1 min, let it stand for 5-9 h, and then centrifuge, wash, and dry to prepare a mesoporous ZIF-8 nanomaterial; (2) N-(4-anilinophenyl)maleimide and 2-mercaptoethanol are dissolved in tetrahydrofuran, and then triethylamine is added. The mixture is stirred at 50-60°C in a nitrogen atmosphere for 5-8 hours. After the reaction is completed, the mixture is rotary evaporated and dried to obtain a hydroxylated antioxidant component. (3) taking the hydroxylated antioxidant component and isophorone diisocyanate into a reactor, adding toluene solvent and dibutyltin diacetate, placing the mixture at 55-70°C and stirring for 5-8 hours, and after the reaction is completed, rotary evaporation and drying are performed to prepare the isocyanate antioxidant component; (4) The mesoporous ZIF-8 nanomaterial is ultrasonically dispersed in toluene, and then the isocyanate-treated antioxidant component is added and stirred to react for 3 to 5 hours. After the reaction is completed, the modified mesoporous ZIF-8 nanomaterial is prepared by filtering, washing, and drying.

4. The low VOC automotive sealing strip composite PVC material according to claim 3, characterized in that: In the step (2), the molar ratio of N-(4-anilinophenyl)maleimide to 2-mercaptoethanol is 1:1-2.

5. The low VOC automotive sealing strip composite PVC material according to claim 3, characterized in that: In the step (3), the molar ratio of the hydroxylated antioxidant component to isophorone diisocyanate is 1-1.2:

1.

6. The low VOC automotive sealing strip composite PVC material according to claim 3, characterized in that: In the step (4), the mass ratio of the mesoporous ZIF-8 nanomaterial to the isocyanate-treated antioxidant component is 1:1-3.

7. A method for preparing a low-VOC automotive sealing strip composite PVC material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing parts by weight of PVC resin, EPDM rubber, modified mesoporous ZIF-8 nanomaterial, composite filler, heat stabilizer, plasticizer and lubricant evenly to form a premix, and then melting and granulating the premix and extruding the premix to prepare a low-VOC automotive sealing strip composite PVC material.

Citation Information

Patent Citations

  • Environment-friendly PVC sealing strip and preparation method thereof

    CN110079034A

  • Micromolecular phosphorus-nitrogen-containing polyol derivative as well as preparation method and application thereof

    CN118754912A